Usability Scale System Implementation as An Effort Improving Personal Engagement on The Official Website of The Study Program at UPN “Veteran” Jawa Timur - Faroqi, Asif; Suryanto, Tri Lathif Mardi; Wulansari, Anita (Nusantara Science and Technology Proceedings, 2023)
In the digital era, websites are a very important online presence for organizations, including universities. A good and professional website can help universities improve their image and reputation, reach a wider range of prospective students, and promote themselves online. Seeing the urgency of a website for tertiary institutions, it is necessary to evaluate it to ensure the expected benefits of the website can be achieved. This study aims to evaluate the usability of the official website of study programs at UPN Veteran Jawa Timur using the System Usability Scale (SUS). Ten official websites of study programs at UPN Veteran Jawa Timur were taken as samples. The results of the usability evaluation show that the average SUS score is 61.4, where the conclusion is marginally low, so it can still be increased to an acceptable level. The results of the usability evaluation with the System Usability Scale (SUS) will be used to design mockup websites for study programs at UPN Veteran Jawa Timur.